PENGARUH EFIKASI DIRI DAN RESILIENSI TERHADAP KOMITMEN PROFESIONAL DIMODERASI BUDAYA KLAN (Studi Kasus pada Guru SMK Negeri di Kabupaten Pati) - hartati, 14.5202.0103; Fauzan, Moh. (Jurnal Mahasiswa Pasca Sarjana, 2016)
The main problem of this research is how the influence of self efficacy and resiliensi to the profesionalcomitment of the teachers of SMK Negeri in Pati regency with moderated by clan culture. The studypopulation were teachers of SMK in Pati regency. The sampling technique uses proportional randomsampling. The number of samples is calculated using the formula Slovin. Collecting data usingquestionnaires. The amount of data that can be analyzed as many as 140. The data were analyzed usingregression-based model of quasi moderator absolute difference. The results showed that (1) professionalcompetence influence on teacher performance, (2) professional commitments do not affect the performanceof teachers, (3) organizational culture does not affect the performance of teachers, (4) organizational culturemoderated the effect of professional competence on teacher performance (5) organizational culturemoderated the effect of professional commitment to teacher performance.Keywords : self efficacy, resiliensy, clan culture, profesional comitment